Negative aging perceptions and cognitive and functional decline: Are you as old as you feel? - Mc Garrigle, Christine; Kenny, Rose; Ward, Mark (My University, 2022)
Background: Research has shown the associations between negative aging perceptions and cognitive and physical decline may be mediated through behavioral and psychological pathways, but they are rarely examined simultaneously. We aimed at assessing the difference in the probability of following a high-, mid-, or low-performing cognitive trajectory, and a high- or low- performing physical function trajectory by negative aging perceptions. We sought to test two competing pathway mechanisms for the associations. Methods: This longitudinal study used data from the Irish Longitudinal Study on Ageing (TILDA), a nationally representative study of community-dwelling adults in Ireland. Adults aged ≥50 years who participated in two or more waves of TILDA (n = 6121) were included. An analysis of the population aged 65 years and above was also conducted (n = 2359). We identified latent class trajectories of Mini-Mental State Examination (MMSE), Instrumental Activities of Daily Living (IADL), ADL, and Timed-Up-and-Go (TUG) performance using Latent Growth Class Analysis (LGCA) on data collected every 2 years over 5 waves. Multinomial logistic regression was used to estimate the likelihood of membership to each trajectory class by negative aging perceptions (APQ). Finally, we tested possible behavioral, psychological, and social mechanisms. Results: LCGA identified three trajectory classes in cognitive and two in each physical function measure. People with the highest tertile of negative APQ were more likely to be in the declining MMSE class and the increasing IADL, ADL, and TUG classes. These associations for cognitive function were partially mediated by psychosocial pathways and for physical function were fully mediated by both psychosocial and health behavior pathways. Conclusions: Negative aging perceptions were associated with cognitive and physical function declines. Poor self-rated health, depressive symptoms, loneliness, and low exercise seem to explain the relationships; however, the possibility of reverse causation remains.
PUBLISHED
Keywords: cognitive function, depression, functional decline, loneliness, longitudinal, mediation, negative aging perceptions, poor self-rated health, Timed Up and Go; Ageing